Genetic Alterations in SMAD4 and K-ras in Serbian Patients With Endometrial Carcinoma. Issue 3 (1st March 2012) - Nikolic, Aleksandra; Ristanovic, Momcilo; Perovic, Vladimir; Trifunovic, Jovanka; Perovic, Milan; Radojkovic, Dragica
Abstract : Objective: This study was aimed at analyzing alterations in K- ras gene and SMAD4 gene promoter in endometrial carcinoma tissue in Serbian patients. Methods/Materials: The study has encompassed 36 patients whose endometrial cancer tissue samples and peripheral blood samples were analyzed for the presence of alterations in the K- ras gene and the SMAD4 gene promoter. The detection of K-ras codon 12 mutation was performed by polymerase chain reaction restriction fragment length polymorphism technique. Analysis of mononucleotide repeat variants at -462T(15) and -4T(12) of the SMAD4 gene promoter was performed by capillary electrophoresis analysis of DNA fragments fluorescently labeled by polymerase chain reaction. Results: Mutation in codon 12 of the K- ras gene was detected with relatively high frequency of 75.0% (27 of 36 cases). Analysis of 2 mononucleotide repeats in the SMAD4 gene promoter showed that in most cases, haplotypes -462T(15)/-4T(12) and -462T(16)/-4T(12) were present; whereas in one case, a novel haplotype -462T(15)/-4T(10) was detected. Conclusions: Findings on the role and potential significance of the K-ras codon 12 mutation and SMAD4 gene promoter variants in patients with endometrial carcinoma remain controversial, and their occurrence in this type of cancer should be further investigated.